Meta-analysis of Cd input-output fluxes in agricultural soil. (September 2022) - Fan, Tingting; Long, Tao; Lu, Yuanyuan; Yang, Lu; Mi, Na; Xia, Feiyang; Wang, Xiaohan; Deng, Shaopo; Hu, Qinghua; Zhang, Fuwang
Abstract: Heavy metal pollution of agricultural soil, especially Cd, has become a global threat to food safety and human health. Analysis of Cd fluxes through different input/output pathways is widely used to predict the change of Cd content in agricultural soil, identify the critical pathways, and assist in developing effective management strategies to protect the environmental quality of agricultural soils. In the present study, literature recording input/output fluxes of Cd through different pathways in agricultural soils were investigated, with study areas primarily located in China, Japan, and Europe. Fluxes of Cd at the study sites were calculated, and comparative analyses were carried out. Results indicated that the dominant input pathway of Cd was strongly associated with the intensity of local industrial activities. Atmospheric deposition was the predominant input pathway of Cd for 75% of the study cases. Irrigation and livestock manure were also major pathways of Cd input in China. The main output pathways were influenced by the planting structure, precipitation, topography, etc. Crop harvesting and leaching to groundwater played important roles among all Cd output pathways in China, and crop harvesting alone could remove a significant amount of Cd from the soil, with an estimated average flux of 6.27 g/ha/yr. Leaching was the dominant Cd output pathway in Europe, accounting for 77%–93% of total outflux. To mitigate the accumulation of Cd in agricultural soil, standards to regulate Cd in the atmospheric environment, irrigation water, and agricultural additives should be tightened, and regulated removal and disposal of crops harvested from the heavily contaminated field should be promoted. Graphical abstract: Image 1 Highlights: The dominant input pathway of Cd in agricultural soils was atmospheric deposition. Crop harvesting is the dominant output pathway in China. Leaching and runoff were also significant output fluxes of Cd. Uncertainty is associated with different monitoring methods and prediction models.